Store-mediated calcium entry in the regulation of phosphatidylserine exposure in blood cells from Scott patients - Munnix, Imke C.A.; Harmsma, Marjan; Giddings, John C.; Collins, Peter W.; Feijge, Marion A.H.; Comfurius, Paul; Heemskerk, Johan W. M.; Bevers, Edouard M. (Thrombosis and Haemostasis, 2003)
Scott syndrome is a bleeding disorder, characterized by impaired surface exposure of procoagulant phosphatidylserine (PS) on platelets and other blood cells, following activation with Ca2+-elevating agents. Since store-mediated Ca2+ entry (SMCE) forms an important part of the Ca2+ response in various blood cells, it has been proposed that deficiencies in Ca2+ entry may relate to the impaired PS exposure in the Scott syndrome. Here, we have tested this hypothesis by investigating the relationship between Ca2+ fluxes and PS exposure in platelets as well as B-lymphoblasts derived from the original Scott patient (M.S.), a newly identified Welsh patient (V.W.) with similar bleeding symptoms, and two control subjects. Procoagulant activity of V.W. platelets in suspension, measured after stimulation with collagen/thrombin or Ca2+-ionophore, ionomycin, resulted in 52% or 17%, respectively, compared to that of correspondingly activated control platelets. Procoagulant activity of V.W. erythrocytes treated with Ca2+-ionophore resulted in less than 6% of the activity of control erythrocytes. Single-cell Ca2+ responses of M.S. and V.W. platelets, adhering to collagen, were similar to those of platelets from control subjects, while PS exposure was reduced to 7% and 15%, respectively, compared to controls. Stimulation of non-apoptotic B-lymphoblasts derived from both patients and controls with Ca2+-ionophore or agents causing Ca2+ mobilization and SMCE, resulted in similar Ca2+ responses. However, in lymphoblasts from M.S. and V.W. Ca2+-induced PS exposure was reduced to 7% and 13% of the control lymphoblasts, respectively. We conclude that i. patient V.W. is a new case of Scott syndrome, ii. Ca2+ entry in the platelets and lymphoblasts from both Scott patients is normal, and iii. elevated [Ca2+]i as caused by SMCE is not sufficient to trigger PS exposure.
Keywords: Procoagulant activity; Scott syndrome; platelets; B-lymphoblasts; intracellular calcium